Performance of high strength lightweight concrete using palm wastes - Huda, Md Nazmul; Jumaat, Mohd Zamin; Islam, Abul Bashar Mohammad Saiful; Al-Kutti, Walid Abubaker (International Islamic University Malaysia, 2018)
The performance of high strength structural lightweight concrete (LWC) using palm wastes, oil palm shell (OPS) as well as palm oil clinker (POC) is of foremost concern. Existing literature used either OPS or POC individually for production of LWC. In this study, both OPS and POC have been put together as coarse aggregate on the way to see the improvement of mechanical properties of waste-based LWC. Regular coarse aggregate has been fully replaced by OPS and POC in the concrete. This structural-grade, lightweight concrete is called palm shell and clinker concrete (PSCC). A series of OPS and POC mixtures have been investigated aimed at identifying better performance. The quantity of OPS and POC mix has been varied as 30, 40, 50, 60 and 70%. Evaluated mechanical properties of PSCC include density, workability, compressive strength at different ages, flexural strength, splitting tensile strength as well as modulus of elasticity. It is revealed that the proposed PSCC has extensive potential in terms of high compressive strength and good material behavior to perform as a better LWC. The study could offer structural lightweight concrete of compressive strength up to 46.47 MPa that is 30.5% higher than the control mix (P100). The usage of 50% OPS to 50% POC coarse aggregate by vol. in the concrete mix is found to be the optimum mix. Furthermore, simple correlation equations have been developed that can be used to predict the compressive strength, splitting tensile strength, flexural strength, modulus of elasticity and ultrasonic pulse velocity of the lightweight concrete using POC. © 2018, International Islamic University Malaysia-IIUM.